P62/Ubiquitin IHC Expression Correlated with Clinicopathologic Parameters and Outcome in Gastrointestinal Carcinomas - Mohamed, Amr; Ayman, Alkhoder; Deniece, Johnson; Wang, Tengteng; Kovach, Charles; Siddiqui, Momin T.; Cohen, Cynthia (Frontiers in Oncology, 2015)
P62 and ubiquitin are small regulatory proteins demonstrated to have implications in the prognosis and survival of various malignancies including: hepatocellular, breast, ovarian, and some gastrointestinal carcinomas. Several trials studied the link of their activity to the extrinsic apoptosis pathway and showed that their autophagy modification has a critical stand point in tumorigenesis. These findings explain their vital role in controlling the process of cell death and survival. It has been shown recently that p62 and ubiquitin overexpression in different types of cancers, such as triple negative breast and ovarian cancers, have directly correlated with incidence of distant metastases. We aim to evaluate p62/ubiquitin expression in gastrointestinal carcinomas of gastric, colonic and pancreatic origin. In gastric carcinoma (45), positive p62 nuclear expression was noted in 53% and cytoplasmic in 57%, while positive ubiquitin was nuclear expressed in 80%, and cytoplasmic in 24%. In colon carcinoma (70), positive p62 nuclear expression was noted in 41% and cytoplasmic in 68.5%, while positive ubiquitin was nuclear in 57% and cytoplasmic in 42%. In pancreatic cancer, positive p62 nuclear expression was noted in 86% and cytoplasmic in 60%, while positive ubiquitin was nuclear in 100% and cytoplasmic in 80%. Normal gastric (6), colon (4) and pancreatic (4) tissues were negative for both P62 and ubiquitin (nuclear and cytoplasmic staining <20%). The results suggest that p62 and ubiquitin are highly expressed in nuclei and cytoplasm of gastric, colonic and pancreatic carcinomas. More studies are needed to correlate IHC expression of p62/ubiquitin with clinicopathologic parameters and overall survival in GI carcinomas.